Design Changes In Residential Reinforced Concrete Buildings: The Causes, Sources, Impacts And Preventive Measures - Mohamad, Mohamad Ibrahim; Nekooie, Mohammad Ali; Harthy, Amur Salim Al- (Penerbit Universiti Sains Malaysia, 2012)
Design changes are common in building projects. Design changes are almost inevitable during the lifecycle of a project; however, design change can be minor or major according to the result. Identifying the source and impact of each design change in the construction lifecycle could help manage all of the design changes associated with a project. Furthermore, such management of changes could help to define preventive measures and actions. A complete survey was conducted using interviews and questionnaires with professionals in three main groups involved in reinforced concrete building projects; all of the sources, causes and impacts were defined by their level of importance. Corrective and preventive actions were measured to avoid as many design changes as possible in this research. The results of this research encourage the implementation of preventive actions by the professionals involved in low-rise reinforced concrete building projects.